Evolving appropriate zinc fertilization strategy for rice-rice (Oryza sativa) cropping system in Cauvery Delta Zone - Rahale, C Sharmila (ORYZA-An International Journal of Rice, 2019)
Six field experiments were conducted at Tamil Nadu Rice Research Institute, Aduthurai to evolve suitable zinc fertilization method for rice - rice (Oryza sativa L.) cropping system in Cauvery delta zone. The treatment includes: T1 : Control, T2 : 100 g zinc sulphate (ZnSO4)/cent in nursery alone., T3 : root dipping alone in 2 % zinc oxide (ZnO) solution, T4 : 25 kg ZnSO4 ha-1, T5 : 37.5 kg ZnSO4 ha-1, T6 : 25 kg ZnSO4 ha-1+ Farm Yard Manure (FYM) 12.5 t ha-1, T7 : 25 kg ZnSO4 ha-1 + Green Leaf Manure (GLM) 6.5 t ha-1, T8 : Tamil Nadu Agricultural University Micro Nutrient (TNAU MN) mixture 25 kg ha-1 as Enriched Farm Yard Manure (EFYM), T9 : TNAU MN mixture 37.5 kg ha-1 as EFYM, T10 : Foliar spray of 0.5% ZnSO4 + 1 % urea at tillering and panicle initiation stage, T11 : 100g ZnSO4 /cent in nursery alone + Foliar spray of 0.5 % ZnSO4 + 1 % urea at tillering and panicle initiation stage (T2+ T10), T12 : root dipping alone in 2 % ZnO solution + Foliar spray of 0.5 % ZnSO4 + 1 % urea at tillering and panicle initiation stage (T3 + T10), T13: 100 g ZnSO4 /cent in nursery alone + root dipping alone in 2 % ZnO solution + Foliar spray of 0.5 % ZnSO4 + 1 % urea at tillering and panicle initiation stage (T2 + T3 + T10). The treatments T5, T6, T7 and T9 were skipped in rabi season to know the residual effect of these treatments in the subsequent season. Among the treatment combinations, application of 25 kg ZnSO4 ha-1 + FYM 12.5 t ha- 1 recorded higher grain yield in both kharif (6232 kg ha-1) and rabi (6236 kg ha-1) seasons. The same treatment combination recorded higher Zn content and Zn uptake as well. Regarding soil nutrient content, the same treatment recorded higher N, P and K content. This treatment was followed by application of 25 kg ZnSO4 ha-1 + green leaf manure 6.5 t ha-1. The experimental findings suggested that combination of organic and inorganic sources not only increased the yield but also improves soil health in Cauvery delta zone.